2017
DOI: 10.2147/cia.s125934
|View full text |Cite
|
Sign up to set email alerts
|

Low FT3: a possible marker of frailty in the elderly

Abstract: IntroductionFrailty is associated with a functional decline of multiple physiological systems, of which they may be a cause or consequence. The objective of the study was to evaluate the prevalence of thyroid hormone modifications in elderly frail subjects and its relationship with frailty.Study population and methodsAn observational study was carried out at the University Hospital “Tor Vergata” in Rome among ambulatory and hospitalized patients. The study population consisted of 112 elderly subjects: 62 were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 47 publications
3
39
1
Order By: Relevance
“…Data presented in this paper derive from the extension of an observational study previously described in Bertoli et al [19], conducted at Tor Vergata University Hospital in Rome on an elderly population and the main aims of which were to evaluate the major markers of frailty and to establish their relationship with changes of the endocrine system observed with ageing [19].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Data presented in this paper derive from the extension of an observational study previously described in Bertoli et al [19], conducted at Tor Vergata University Hospital in Rome on an elderly population and the main aims of which were to evaluate the major markers of frailty and to establish their relationship with changes of the endocrine system observed with ageing [19].…”
Section: Methodsmentioning
confidence: 99%
“…All patients participating to the study protocol underwent clinical examination, anthropometric parameters (weight and height) were recorded and body mass index (BMI) was calculated. All participants received a multidimensional geriatric evaluation, as previously described [19], and underwent blood sampling for blood cell count, plasma concentrations of glucose, glycosylated haemoglobin (HbA1c), blood urea nitrogen (BUN), creatinine, sodium, potassium, calcium, phosphorus and magnesium, total cholesterol, high-density lipoprotein (HDL) cholesterol, low-density lipoprotein (LDL) cholesterol, triglycerides, albumin, parathyroid hormone (PTH), 25-hydoxyvitamin D (25OHD), osteoprotegerin (OPG), bone alkaline phosphatase (BAP), osteocalcin (OC), Cterminal cross-linked telopeptide of type I collagen (CTX), thyroid stimulating hormone (TSH), free triiodothyronine (FT3), free thyroxine (FT4), adrenocorticotropic hormone (ACTH), cortisol, dehydroepiandrosterone sulphate (DHEAS), testosterone, estradiol, sex hormone binding globulin (SHBG), growth hormone (GH), insulinlike growth factor-1 (IGF-1), insulin-like growth factor binding protein-3 (IGFBP-3), interleukin-6 (IL-6), tumor necrosis factor-a (TNF-a), high sensitivity C reactive protein (hs-CRP).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The importance of DHEAS in the pathogenesis of frailty may be most relevant as part of a generalised endocrine dysfunction (79). A 2017 study reported a significant inverse correlation between FT3 and frailty score in elderly subjects (n=112, 62 inpatients with hip fracture and 50 outpatient controls) (113). The study used the 'Survey of Health, Ageing and Retirement in Europe Frailty Instrument (SHARE-FI) to generate the frailty score with an r of -0.436 and P<0.001 when correlated with FT3.…”
Section: Subsequent Rcts Of Testosterone Treatment Have Reported Outcmentioning
confidence: 99%